A Clustering Approach to Understanding Farmers' Success Strategies. (18th August 2020) - Etumnu, Chinonso; Gray, Allan W.
Abstract: This paper examines the prioritization of management factors by farmers that lead to the success of their farm business. The research also examines the heterogeneity of producer prioritization of different success strategies. Using a hierarchical clustering approach, we found that each farmer group prioritizes either managing costs, managing output prices, managing people, managing production, or managing assets. The results indicate that the farmer groups are heterogeneous in their prioritization of five strategic management factors. These results provide useful insights for farmers, farm input providers, and farm service providers.